Prodominance and Incidence of Pseudomonas Bacteria in Urinary Samples from Women with Chronic Urinary Tract Infections: Dominasi dan Insidensi Bakteri Pseudomonas pada Sampel Urin dari Wanita dengan Infeksi Saluran Kemih Kronis - Saleem, Hanan Kareem (Universitas Muhammadiyah Sidoarjo, 2024)
Background; Chronic urinary tract infections in women are often associated with Pseudomonas aeruginosa, a significant pathogen causing recurrent and persistent infections. Aims of the study; To assess the predominance and incidence of Pseudomonas aeruginosa in urinary samples from women with chronic urinary tract infections. Methodology; A cross-sectional study at Al-Habbobi Teaching Hospital (10/11/2023–11/11/2024) examined bacterial infections in urinary samples from 1000 UTI patients (aged 35–45). Samples were cultured and analyzed for bacterial identification and antimicrobial susceptibility. Sociodemographic and clinical data were collected using questionnaires, ensuring ethical compliance and participant confidentiality. Result; The study included 1000 participants, with 60% in the 35–40 age group, 75% married, 60% having a college education, and 50% employed. Forty percent had a UTI history of 1–3 years. The most common bacteria in urine samples were Escherichia coli (45%), followed by Pseudomonas aeruginosa (22%), Klebsiella pneumoniae (15%), and Enterococcus faecalis (7%). Infection rates of Pseudomonas aeruginosa were highest in patients with UTIs lasting 4–7 years (40.91%), followed by those with >7 years (36.36%) and 1–3 years (22.73%). The 35–40 age group had the highest prevalence of Pseudomonas (59.09%). Conclusions; The study concludes that Escherichia coli and Pseudomonas aeruginosa are the most prevalent bacteria in UTIs, with Pseudomonas being more common in patients aged 35–40 and with longer infection durations. Highlights: Chronic UTIs often involve Pseudomonas aeruginosa, causing persistent infections. Escherichia coli (45%) and Pseudomonas aeruginosa (22%) dominate UTI pathogens. Pseudomonas prevalence increases with age (35–40) and longer infection durations. Keywords: Escherichia coli, Pseudomonas aeruginosa, Urinary tract infections (UTIs), Chronic infections, Biofilms, Antibiotic resistance